2020
DOI: 10.1038/s41598-020-73575-2
|View full text |Cite
|
Sign up to set email alerts
|

High aspartate aminotransferase to alanine aminotransferase ratio on admission as risk factor for poor prognosis in COVID-19 patients

Abstract: This study aimed to analyze aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio in COVID-19 patients. After exclusion, 567 inpatients were included in this study and separated into two groups according to their AST/ALT ratio on admission. Death was regarded as poor prognosis in this study. Of 567 patients, 200 (35.3%) had AST/ALT ≥ 1.38. Of the 200 patients, older age (median age 60 years), myalgia (64 [32%] cases), fatigue (91 [45.5%] cases), some comorbidities and outcomes were significa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 34 publications
2
33
1
Order By: Relevance
“…Although severe COVID-19 is an inflammation-driven disease, leukocyte cell count was the only traditional inflammatory marker that was weakly associated with mortality, whilst neither the SOFA score nor other commonly used laboratory parameters like CRP and PCT were able to significantly identify high-risk patients. In addition, three previously published risk scores that are based on a variety of different traditional diagnostic parameters 5 , 7 , 8 failed to significantly predict mortality in our COVID-19 cohort.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Although severe COVID-19 is an inflammation-driven disease, leukocyte cell count was the only traditional inflammatory marker that was weakly associated with mortality, whilst neither the SOFA score nor other commonly used laboratory parameters like CRP and PCT were able to significantly identify high-risk patients. In addition, three previously published risk scores that are based on a variety of different traditional diagnostic parameters 5 , 7 , 8 failed to significantly predict mortality in our COVID-19 cohort.…”
Section: Discussionmentioning
confidence: 61%
“…S8 ). In addition, we tested three previously published COVID-19 mortality risk scores 5 , 7 , 8 ; none of these scores showed a significant prediction of mortality in our patient cohort (supplementary Fig. S9 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of recently published studies reveals the role of systemic vasculitis and cytokine-mediated coagulation disorders, predominantly responsible for multi-organ failure in patients with severe COVID-19 complications. The hematological (lymphocyte count 11 , 12 , neutrophil count 13 , neutrophil–lymphocyte ratio (NLR)) 14 , 15 , inflammatory (C-reactive protein (CRP)) 16 , immunological (interleukin (IL)-6) 17 and biochemical (D-dimer 18 , troponin, creatine kinase (CK) 19 biomarkers, as well as procalcitonin (PCT) 16 , 20 , erythrocyte sedimentation rate (ESR) 21 , aspartate aminotransferase (AST)) 22 , and those particularly related to coagulation cascades in disseminated intravascular coagulation (DIC) 23 and acute respiratory distress syndrome (ARDS) 24 have been reported to be important biomarkers associated with COVID-19 disease. New laboratory biomarkers could be identified through the accurate analysis of multicentric case series; in particular, homocysteine and angiotensin II could play a significant role in this regard 24 .…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated the relationship between impaired liver function and longer hospitalization days. Qin et al found that a high level of AST or ALT might be the prediction of a worse prognosis in COVID-19 patients 16 . Also, Lei et al analyzed COVID-19 patients for liver enzymes and found that elevated AST was strongly associated with the mortality risk 17 .…”
Section: Discussionmentioning
confidence: 99%